Sago Bark as Renewable Energy - Chong, K.H; Law, P.L; Rigit, A.R.H.; Baini, R.; Shanti, F.S (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Much research has been done on the determination of the heating value of biomass waste, but currently no research is being done on the heating value of sago bark. In Malaysia, sago bark is an abundant waste product from sago starch extraction. This study presents the moisture content and heating value determination of paddy straw, empty fruit bunch (EFB), sago bark, oil palm kernel shell (OPKS), and wood chips. The moisture content and heating value of the investigated biomass were determined according to the British Standard EN 1477-2:2009 and bomb calorimeter, accordingly. It was observed that paddy straw recorded the highest moisture content at 97.75% wt. This was followed by EFB 95.34% wt., sago bark 96.05% wt., OPKS 95.28% wt. and wood chips 11.61% wt. In the dry state, wood chips had the highest heating value, with a value recorded as approximately 22.41 MJ kg-1, followed by OPKS 21.40 MJ kg-1, sago bark 19.56 MJ kg-1, EFB 17.82 MJ kg-1 and paddy straw 15.33 MJ kg-1. Current experimental trials suggest that the heating value of sago bark makes it suitable for use for co-firing with coal power generation